FEATURES OF MANIFESTATION OF FINANCIAL DECENTRALIZATION AT THE REGIONAL LEVEL: COMPARATIVE ANALYSIS OF DOMESTIC AND WORLD PRACTICE - Жеребило, Ірина (Socio-economic relations in the digital society, 2019)
An important determinant of socio-economic development is fiscal decentralization, which promotes the one hand, reducing the state’s role in their financial support on the other — creates opportunities for strengthening the autonomy of local governments. Based on the analysis of the best practices developed economies reveals peculiarities of fiscal decentralization in the context of its impact on economic growth of regions and local communities. The sources of income  formation are revealed. We show that budget revenues form the subregional level (the vast majority), local taxes, a signifi cant proportion of which are property taxes, and in federal countries their importance in budget revenues is much lower than in unitary. Different countries have a different degree of decentralization, but «richer» countries are more decentralized. It has been proved that there is no optimal level of financial decentralization, because each country goes its own way of development. Isolate the causes of fiscal decentralization, including the following: the low efficiency of the education, health, social security, public administration; Excessive maintenance costs for network and management; temypy unsatisfactory implementation of new technologies, small communities can not desire to increase the efficiency and quality of public services, although in the early 2000s for Eastern Europe were the priority tasks of building their democratic political system. The first steps of financial decentralization in Ukraine are highlighted and the shortcomings of the initiated reform are shown. The priorities of budget policy in Ukraine in the conditions of the reform of inter-budgetary relations are determined. It is emphasized that it is inappropriate to mirror the transfer of experience in implementing the reform of financial decentralization in countries of Europe and the world on the territory of Ukraine. The above requires a detailed analysis of the peculiarities of its manifestation within each country.
Keywords: fiscal decentralization; local taxes; local governments; community; region; European Union countries